2003
DOI: 10.1067/mtc.2003.75
|View full text |Cite
|
Sign up to set email alerts
|

Appropriate timing of surgical intervention after transmural acute myocardial infarction

Abstract: Coronary revascularization within 3 days of a transmural acute myocardial infarction might be an added risk for mortality. In the absence of absolute indications for emergency surgical intervention, such as structural complications and ongoing ischemia, a 3-day waiting period before surgical revascularization should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
61
1
16

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(82 citation statements)
references
References 22 publications
4
61
1
16
Order By: Relevance
“…When patients do not present with an absolute surgical indication, a 3-day waiting period should be considered before CABG. 1,6) In our study, the time interval from AMI onset to CABG was 10 ± 12 and 31 ± 19 days in patients who underwent only CABG and CABG following PCI, respectively. These long intervals are attributed to the no in-hospital mortality and the equivalent complication incidences to the non-AMI patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When patients do not present with an absolute surgical indication, a 3-day waiting period should be considered before CABG. 1,6) In our study, the time interval from AMI onset to CABG was 10 ± 12 and 31 ± 19 days in patients who underwent only CABG and CABG following PCI, respectively. These long intervals are attributed to the no in-hospital mortality and the equivalent complication incidences to the non-AMI patients.…”
Section: Discussionmentioning
confidence: 99%
“…A drug-eluting stent is now applied to an LMT lesion and demonstrates equivalent mortality and complications to CABG. 12,13) The number of stent implantations to an LMT lesion for AMI will increase when the risk of re-stenosis is eliminated and would reduce the mortality of emergent CABG, which was reported as 7.9%-14.2% and 9.8%-19.2% 2,6) in previous large studies. It is reported that a drug-eluting stent reduced the re-intervention rate compared to the bare-metal stent.…”
Section: Discussionmentioning
confidence: 99%
“…De maneira geral, a revascularização cirúrgica de urgência é indicada em pacientes com anatomia coronária favorável, quando houver contraindicação ou falhas das terapêuticas trombolítica e de revascularização percutânea na presença de complicações, tais como isquemia recorrente, choque cardiogênico e complicações mecânicas do infarto 37,232 . Paralelamente, a cirurgia de revascularização tem sido indicada de forma eletiva, de acordo com critérios clássicos, a partir de 3-7 dias após o episódio do infarto 334,335 . eram empregados no tratamento intervencionista 169 .…”
Section: -Revascularização Cirúrgicaunclassified
“…However, there is no consensus in the literature regarding this point 6 . Some groups wait for up to 30 days after AMI before revascularization in an attempt to prevent potential complications that may arise during the recovery period following myocardial infarction 6 .…”
mentioning
confidence: 93%
“…Since the 1970s, studies have been made to determine the optimal timing of coronary artery bypass graft surgery (CABG) after acute myocardial infarction (AMI) with less operative risk [1][2][3][4][5][6][7] . However, there is no consensus in the literature regarding this point 6 .…”
mentioning
confidence: 99%